(Table 1) Geochemistry of volcanic glass shards from tephra layers of the Gulf of Aden and in the Turkana Basin - Sarna-Wojcicki, Andrei M; Meyer, C E; Roth, Peter H; Brown, F H (Supplement to: Sarna-Wojcicki, AM et al. (1985): Ages of tuff beds at East African early hominid sites and sediments in the Gulf of Aden. Nature, 313(6000), 306-308, https://doi.org/10.1038/313306a0, 1985)
The early hominids of East Africa were dated by determining the ages of tuff beds at the sites. Despite much research using palaeomagnetic and K/Ar-dating techniques, some of those ages are still controversial (Brown, 1982, doi:10.1038/300631a0; Aronoson et al., 1983, doi:10.1038/306209c0). To obtain independent age estimates for these tephra layers, we have examined cores from DSDP Sites 231 and 232 in the Gulf of Aden which consist mainly of calcareous nannofossil ooze, but also contain rare tephra horizons (Brunce and Fisher, 1974, doi:10.2973/dsdp.proc.24.101.1974) dated by interpolation from the established nannofossil stratigraphy. Chemical analysis confirms that the identity and sequence of these horizons is the same as that at the East African sites. We conclude that the age of the Tulu Bor Tuff is <3.4 Myr and hence that the Hadar hominid specimens are also <~3.4 Myr old.